Communication Skills Training in Medicine Degrees at Andalusias's Public Universities: An Ethical Matter - Porras Florido, Carolina Patricia; Becerra-Muñoz, Elena; Victoria-Mas, Juan Salvador (Universidad Ramón Llull, 2020)
In contexts where communication skills can be learnt and taught, they become an ethical matter as far as the proper provision of healthcare is concerned. Communication skills bestow greater empathy to exchanges with the patients and they are necessary to improve the ways of relationship between physicians and patients. This study analyses the Medicine degrees program at public univer sities in Andalusia. This study takes this Spanish region as a reference to evaluate the communication training in Public Medicine Schools, and offers them some suggestions to improve medical skill communi cation. The multidisciplinary dimension of communication skills training could be a vital tool in encouraging certain types of patient behaviour. The ever-increasing frequency of assaults by patients on the medical staff attending them are the ultimate proof that this dimension is currently lacking.
Keywords: Medicina - Estudio y enseñanza superior; Médicos y pacientes; Comunicación en medicina; Physician-patient relationship; Communication skills training; Communication and Medicine; Public university; Social health responsibility; Andalusia; Andalusian medical training; Medicine ethics